Nursing the Economic Miracle Patient Named Kenya - Ouma Denis (International Journal of Economics, Business and Innovation Research, 2026)
Demographics dividends are derived from management of population characteristics. It is a result of complex components and rationales measurable and non-measurable. The Kenyan economy is an economic miracle. The country’s economy has been able to positively respond to almost all the measures incorporated in demographics. Its economic variable relationship is a good case study of the benefits of demographics management as advanced by the UN as countries focus on dependency, productivity, savings investment and social challenges in relation to population characteristics. Analysis of Kenya's demographics variables is carried out using panel data for the period 1960-2020. Results from the analysis show significant resilient in the Kenyan economy with policy injections giving positive results. The study proposes the adoption of a dividend support tool to assist the country to maintain the recorded trajectory away from the contradicting results of most African countries. The findings present new insights that positively support the notion of economic growth derived from population characteristics supported by good governance.